Legal Position and Responsibilities of Translators Sworn in Translation of Notarial Certificate on Letter of Authorization (LOA) Guide - Pandu Artha Waskitamukti; Hari Purwadi; Sapto Hermawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The purpose of this study is to analyze the role and legal position of sworn translators in translating Notarial Certificates related to the Letter of Authorization (LOA), as well as to address the legal implications of translation errors. This research employs a normative legal study method that includes a legislative and conceptual approach, bolstered by case studies such as that of the Nature Republic brand. The findings indicate that sworn translators play a crucial role in ensuring the accuracy and clarity of international legal documents within the Indonesian legal system. However, the regulations concerning the position and legal responsibilities of sworn translators remain incomplete, leading to legal uncertainties. Translation errors can create barriers to law enforcement and the protection of legal rights for the involved parties. Therefore, there is a need for clearer regulations regarding professional standards in this field.